2006
DOI: 10.1124/dmd.106.010132
|View full text |Cite
|
Sign up to set email alerts
|

Use of Immortalized Human Hepatocytes to Predict the Magnitude of Clinical Drug-Drug Interactions Caused by CYP3A4 Induction

Abstract: ABSTRACT:Cytochrome P4503A4 (CYP3A4) is the principal drug-metabolizing enzyme in human liver. Drug-drug interactions (DDIs) caused by induction of CYP3A4 can result in decreased exposure to coadministered drugs, with potential loss of efficacy. Immortalized hepatocytes (Fa2N-4 cells) have been proposed as a tool to identify CYP3A4 inducers. The purpose of the current studies was to characterize the effect of known inducers on CYP3A4 in Fa2N-4 cells, and to determine whether these in vitro data could reliably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
106
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 25 publications
6
106
1
Order By: Relevance
“…In our transactivation studies in DPX-2 cells, a wide enough array of antibiotic concentrations was used to permit EC 50 and E max estimates that could then be used to compute a RIS (Ripp et al, 2006). By using this strategy, we identified seven of 21 (33%) antibiotics with RIS values that would predict clinically significant enzyme induction (i.e., decrease in target drug area under the curve) using the following RIS criteria (ours): likely, if an RIS score was from 0.1 to 0.5.; possible, for an RIS from 0.05 to 0.1; and not likely for an RIS Ͻ0.05.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…In our transactivation studies in DPX-2 cells, a wide enough array of antibiotic concentrations was used to permit EC 50 and E max estimates that could then be used to compute a RIS (Ripp et al, 2006). By using this strategy, we identified seven of 21 (33%) antibiotics with RIS values that would predict clinically significant enzyme induction (i.e., decrease in target drug area under the curve) using the following RIS criteria (ours): likely, if an RIS score was from 0.1 to 0.5.; possible, for an RIS from 0.05 to 0.1; and not likely for an RIS Ͻ0.05.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Relative induction scores (RIS) were computed as described by Ripp et al (2006), using prior published values for C max and fraction unbound to calculate C max unb .…”
Section: Reagentsmentioning
confidence: 99%
“…In addition, expression of PXR and AhR, which are important transcription factors involved in the regulation of drug-metabolizing enzymes and transporters, have been detected in Fa2N-4 cells (Mills et al, 2004). Ripp et al (2006) further characterized Fa2N-4 cells by evaluating the effect of selected compounds on CYP3A4 induction and comparing in vitro induction data with in vivo induction response. It was suggested that Fa2N-4 cells could be used to identify CYP3A4 inducers as well as to predict the magnitude of clinical drug-drug interactions.…”
mentioning
confidence: 99%
“…For instance, CYP3A4 induction by selective CAR activators was not evaluated in Fa2N-4 cells (Ripp et al, 2006). Furthermore, the expression of major drug-metabolizing enzymes, nuclear receptors, and hepatic transporters in these cells are also not known.…”
mentioning
confidence: 99%
“…The fact that appropriate pharmacology terminology and concepts apply to P450 induction studies is demonstrated in a recent publication. Ripp et al (2006) related in vitro induction data (E max and EC 50 values) of 24 drugs, obtained in induction studies using Fa2N-4 cells, with their efficacious free plasma concentrations and calculated a relative induction score. This score correlated highly (r 2 values Ͼ0.92) with decreases in area under the plasma concentration versus time curve values for coadministered CYP3A4 object drugs (midazolam or ethinylestradiol) from previously published clinical drug-drug interaction studies.…”
mentioning
confidence: 99%